2022
DOI: 10.12688/f1000research.110889.1
|View full text |Cite
|
Sign up to set email alerts
|

‘Comparison and correlation of the maxillary sinus dimensions in various craniofacial patterns: A CBCT Study’

Abstract: BACKGROUND  To compare and correlate the maxillary sinus dimensions and basal bone height among various facial patterns using CBCT for advanced diagnosis and treatment planning in Orthodontics. METHODS 66 CBCT images within age group of 18-30 years were divided into horizontal (Group 1), average (Group 2) and vertical (Group 3) facial growth patterns. Maxillary sinus dimensions were compared and correlated in all three groups. The sinus height and basal bone height were recorded at 3 locations-between 1st prem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This is an anatomical limitation that may hinder the mobility of teeth during orthodontic treatment and lead to complications. Any change in the maxillary sinus' growth could consequently result in the development of skeletal or dental malocclusion [3] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is an anatomical limitation that may hinder the mobility of teeth during orthodontic treatment and lead to complications. Any change in the maxillary sinus' growth could consequently result in the development of skeletal or dental malocclusion [3] .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Kumar et al compared and correlated the maxillary sinus dimensions and basal bone height among various facial patterns using CBCT images. They came to the conclusion that there is a relationship between the height of the basal bones and the maxillary sinuses with the facial pattern, which should be taken into account while planning orthodontic treatments and performing facial growth modification procedures on younger patients [3] . Moreover, Przystańska et al retrospective analysis of head CT scans revealed a correlation between midface dimensions and all measurements of the maxillary sinuses [7] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations